2020
DOI: 10.1111/nph.16969
|View full text |Cite
|
Sign up to set email alerts
|

Increasing axial parenchyma fraction in the Malagasy Magnoliids facilitated the co‐optimisation of hydraulic efficiency and safety

Abstract: Summary The evolution of angiosperms was accompanied by the segregation and specialisation of their xylem tissues. This study aimed to determine whether the fraction and arrangement of parenchyma tissue influence the hydraulic efficiency–safety trade‐off in the basal angiosperms. We examined xylem anatomical structure and hydraulic functioning of 28 woody species of Magnoliids in a tropical rainforest of Madagascar and reported, for the first time, quantitative measurements that support the relationship betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 107 publications
(175 reference statements)
1
17
1
Order By: Relevance
“…The amount of NSCs was also greater in angiosperms than in gymnosperms, which translated into different associations between NSCs and RAP. In conifers, the proportion of axial parenchyma that constitutes secondary xylem is usually much lower than that of angiosperms (Spicer, 2014;Aritsara et al, 2020), although we found no significant differences. This configuration may emphasize the role of axial parenchyma in maintaining water transport in the angiosperm vessels (Spicer, 2014).…”
Section: Relationships Between Nscs and Rap Fractionscontrasting
confidence: 73%
See 2 more Smart Citations
“…The amount of NSCs was also greater in angiosperms than in gymnosperms, which translated into different associations between NSCs and RAP. In conifers, the proportion of axial parenchyma that constitutes secondary xylem is usually much lower than that of angiosperms (Spicer, 2014;Aritsara et al, 2020), although we found no significant differences. This configuration may emphasize the role of axial parenchyma in maintaining water transport in the angiosperm vessels (Spicer, 2014).…”
Section: Relationships Between Nscs and Rap Fractionscontrasting
confidence: 73%
“…It has been suggested that axial parenchyma can influence hydraulic capacitance in angiosperms by releasing water into vessels in periods of drought (Morris et al, 2018). Additionally, vessel to axial parenchyma connectivity would facilitate xylem hydraulic optimization, suggesting that plants may need axial parenchyma to surround and service vessels (Aritsara et al, 2020; Ziemińska et al, 2020). Therefore, the physiological function of both types of parenchyma could be very different, calling for a careful consideration of xylem structure for a better understanding of tree ecological strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the recovery of hydraulic conductivity is less dependent on stored carbon. This opposing strategy may also be related to the different functions performed by RAP in roots and stems (Zheng & Martínez‐Cabrera, 2013; Secchi et al ., 2017; Aritsara et al ., 2021). In agreement with Morris et al .…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with our current observations that as the available water increases, plants choose to widen the diameter of vessels or tracheids downstream (i.e., in branches) of the water transport pathway, therefore, matches the usually wider conduits upstream (i.e., in roots) of the pathway, to enable their branches to get stronger competitiveness for light and carbon uptake (Pfautsch et al ., 2016). The safety versus efficiency trade-off theory in the xylem claimed that when the tension to pull sufficient water and transport through the stem exceeds the physical limits, the risk of cavitations in the xylem of branches will inevitably increase (Tyree & Zimmermann, 2002;Aritsara et al ., 2021;. This will gradually reduce the gap with the cavitation vulnerability in roots, resulting in the decrease ofP 50 root -branch along environmental aridity gradients.…”
Section: Ai Drives Hydraulic Vulnerability Segmentation By Affecting ...mentioning
confidence: 99%